Communiquer l’invisible - Catherine Côté (Glad!)
Chronic pain affects approximately one in four people in Canada, with a higher proportion of women. Although women are overrepresented in many pain conditions and experience more severe, more frequent, more diffuse, and more disabling pain, chronic pain does not seem to have been conceptualized as a feminist issue. This article uses an auto-ethnographic approach to analyze how the daily experience of chronic pain is a feminist issue. Two main themes are analyzed through the author’s daily experience of chronic pain, namely 1) the difficulties related to the recognition of pain, particularly important for women and people belonging to other marginalized groups or standing at the intersection of various identities, and 2) the reinforcement of chronic pain experience by different oppression systems such as classism, capitalism, ableism, and patriarchy.